Differential psychophysiological effects of operant and cognitive behavioural treatments in women with fibromyalgia. (15th June 2016) - Thieme, K.; Turk, D.C.; Gracely, R.H.; Flor, H.
Abstract: Background: Determination of psychophysiological effects of operant behavioural (OBT) and cognitive behavioural treatment (CBT) for fibromyalgia patients. Methods: One hundred and fifteen female patients randomized to OBT ( N = 43), CBT ( N = 42), or whole‐body infrared heat (IH) ( N = 30) were compared before and after group treatment as well as at 6‐ and 12‐month follow‐ups using intent‐to‐treat analysis (12 drop‐outs). Thirty matched pain‐free controls (CON) served as reference group for the initial psychophysiological analysis. Surface electromyogram (EMG), blood pressure, heart rate (HR) and skin conductance levels (SCL) were continuously recorded during adaptation, baseline, social conflict, mental arithmetic and relaxation tasks. Results: At baseline, fibromyalgia patients showed higher SCL and HR, lower diastolic blood pressure and EMG in comparison to controls. OBT and CBT compared to IH significantly reduced pain intensity [OBT: effect size (ES) = 1.21 CI: 0.71–1.71, CBT: ES = 1.23, CI: 0.72–1.74]. OBT increased diastolic blood pressure [ES = 1.13, CI: 0.63–1.63 and CBT reduced SCL (ES) = −0.66, CI: −1.14–0.18] 12 months after treatment. Both CBT and OBT significantly increased EMG levels (OBT: ES = 0.97, CI: 0.48–1.46, CBT: ES = 1.17, CI: 0.67–1.68). In contrast, the IH group did not show any significant changes in the psychophysiological parameters. Conclusion: Increased diastolic blood pressure and decreased pain after OBT suggest a reactivation of baroreflex‐mechanisms in fibromyalgia and a normalization of the blood pressure and pain functional relationship. Reduced SCL following CBT may indicate reduced general arousal levels. Increased muscle tension after CBT and OBT suggest a normalization of physical parameters. The reduction in pain seems to be mediated by different psychophysiological processes, providing support for mechanism‐based treatments might be indicated for CBT and OBT. What does this study add?: Differential physiological stress responses followed different psychological interventions. While OBT influenced blood pressure by restoring blood pressure‐pain interaction, CBT reduced stress‐related sudomotor activity. These results implicate specific mediating mechanisms in fibromyalgia suggesting a basis for matching based on specific patient psychophysiological features.